2014
DOI: 10.5498/wjp.v4.i4.120
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and sex/gender differences in youth suicidal behavior

Abstract: Suicide is the second leading cause of death in youth globally; however, there is uncertainty about how best to intervene. Suicide rates are typically higher in males than females, while the converse is true for suicide attempts. We review this "gender paradox" in youth, and in particular, the age-dependency of these sex/gender differences and the developmental mechanisms that may explain them. Epidemiologic, genetic, neurodevelopmental and psychopathological research have identified suicidal behaviour risks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 140 publications
5
68
1
6
Order By: Relevance
“…25 While some studies showed either a higher rate either among boys 7 or among girls, 15,26 our study found gender difference is insignificant, which was also found in other studies. 8,27,28 Rhodes et al 25 presented a comprehensive discussion on the reasons and timing of the gender effects in the prevalence and lethality of suicidal behaviours. The inconsistent findings might be partially explained by the shift in the interactive social network during adolescent development.…”
Section: Discussionsupporting
confidence: 74%
“…25 While some studies showed either a higher rate either among boys 7 or among girls, 15,26 our study found gender difference is insignificant, which was also found in other studies. 8,27,28 Rhodes et al 25 presented a comprehensive discussion on the reasons and timing of the gender effects in the prevalence and lethality of suicidal behaviours. The inconsistent findings might be partially explained by the shift in the interactive social network during adolescent development.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with other studies, males generally displayed higher suicide rates than females, with the exception of earlier adolescence (10-14 years); however, females are more frequently admitted to hospital for self-inflicted injuries (the "gender paradox" of suicidal behaviour). 28 Over the life course, male suicide rates were observed to steadily increase beginning in adolescence, peaking first during middle adulthood and again among seniors 80 years and older; the same pattern was also observed among females, albeit of a lesser magnitude.…”
Section: Discussionmentioning
confidence: 83%
“…Research on injuries tended to focus solely on gender differences with the exception of research on suicide which has a well-developed body of literature on the role that masculinity plays in suicide. Several recent articles argue that suicide rates among men are persistently higher than among women due to the difficulty they face attaining traditional masculine norms, including personal autonomy and socio-economic security [5052]. Further, researchers suggest that adhering to certain masculine norms that discourage help-seeking when emotionally distressed further encourage suicidal behaviors among men [53, 54].…”
Section: Gender and Health Behaviorsmentioning
confidence: 99%